2019
DOI: 10.1093/ijtj/ijy035
|View full text |Cite
|
Sign up to set email alerts
|

‘Irreversible’: The Role of Digitization to Repurpose State Records of Repression

Abstract: 1Since mid-2005, archivist-activists at the Historical Archive of the National Police of Guatemala have been digitizing a century's worth of previously suppressed police records so as to protect, mobilize and provide access to them -23 million pages to date. We find that digitization amplified the staff's repurposing of the archive to serve victims of human rights violations. Digitization enhances short-and long-term safeguards for the archive's physical integrity, probative value and enduring accessibility, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…However, the logic of connectivity may raise questions as to the politics inherent in digitization processes, particularly concerning the impact of mass digitization on local cultural knowledge (Guberek et al, 2019;Thylstrup, 2019). The post-custodial approach, developed by critical librarians and archivists, seeks to establish digital archiving practices that both redistribute resources and empower communities as owners of their documentary heritage (Alpert-Abrams et al, 2019).…”
Section: Connectivity: Archives Archivists and The Publicmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the logic of connectivity may raise questions as to the politics inherent in digitization processes, particularly concerning the impact of mass digitization on local cultural knowledge (Guberek et al, 2019;Thylstrup, 2019). The post-custodial approach, developed by critical librarians and archivists, seeks to establish digital archiving practices that both redistribute resources and empower communities as owners of their documentary heritage (Alpert-Abrams et al, 2019).…”
Section: Connectivity: Archives Archivists and The Publicmentioning
confidence: 99%
“…It emphasizes that data are never truly raw; rather, they are always produced, curated, preserved, and presented within specific contexts. In this spirit, Guberek et al (2019) highlighted the significant, often irreversible effects of simplistic and expedient digitization methods, particularly when implemented under conditions of armed conflict and human rights crises. Complementing this, Thylstrup (2019) observed that mass digitization may give rise to new cultural memory institutions on the web.…”
Section: Datafication Of Heritage and Future Memorymentioning
confidence: 99%
“…There are a multitude of theoretical framings for these archival practices. For example, in community archives the communities about whom the archive is developed play a central role in its development, and in activist archives the practice of archiving or tagging artefacts in the archive may be seen as activism in itself (see, for example, [30,31,56]). Each of these approaches aims to highlight different aspects of justice issues, and are made up of extensive and nuanced bodies of work related to theoretical, methodological, as well as practical explorations which we do not detail herein.…”
Section: Digital Archives and Anti-stigma Workmentioning
confidence: 99%
“…Our work sits alongside this kind of justice-oriented work, which aims to promote the development of archives that are explicitly political and antiviolent [3,25], and that place important aspects of community, activism, and justice at their core [30,31,56]. Allard and Ferris have written about social justice and community mobilisation through participatory approaches to archiving in their Digital Archives and Marginalized Communities Project [3].…”
Section: Digital Archives and Anti-stigma Workmentioning
confidence: 99%
“…The literature describes a number of obstacles in human rights organisations, including children and forced labour, low or poor remuneration, sexual harassment, and the safety of women workers, which are essential within the justice system (Guberek et al, 2019 ). Some managers fear that if digitalisation were implemented, the issues would emerge and jeopardise the corporate image (Larsson, 2021 ).…”
Section: Introductionmentioning
confidence: 99%